An epidemiological study of postnatal depression among women availing maternal health services in rural areas of Belagavi, Karnataka, India - K., Kruthika; Udayar, Sharavanan Eshwaran; Mallapur, M. D. (International Journal Of Community Medicine And Public Health, 2017)
Background: Postnatal depression is an important public health issue exhibiting the strongest link to adverse child outcomes and also maternal morbidity. Objectives were to study the prevalence of Postnatal depression among mothers and to identify the factors associated with depressive symptoms among post-natal mothers. Methods: The present cross sectional study was conducted from January 2016 to June 2016 in two rural areas among 300 women attending immunisation clinics in the Primary health centre with postpartum period less than 3 months were included in the study. Edinburgh Postnatal depression scale was used to for identifying mothers at risk of postnatal depression. A score of ≥13 was considered as positive for depressive symptoms. Results: The prevalence of Post-natal depression 41 (13.6%). Factors like age, literacy status, socio economic status, gravidity, sex of newborn, mode of delivery and unplanned pregnancy were significantly associated with the prevalence of postnatal depression. Conclusions: Early screening of the women and counselling of women and their family will reduce the maternal morbidity and adverse child outcomes.